2018
DOI: 10.1177/1524838018813198
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Mental Disorders Associated With Sexual Assault: A Meta-Analysis

Abstract: Sexual assault (SA) is a common form of trauma that is associated with numerous deleterious outcomes. Understanding the relative prevalence of psychiatric diagnoses in people who have been sexually assaulted versus people who have not been assaulted could help to prioritize assessment and intervention efforts, but there has been no quantitative review of this topic. A search of PsychINFO, ProQuest Digital Dissertations and Theses, and Academic Search Premier for articles dated between 1970 and 2014 was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 92 publications
8
93
2
4
Order By: Relevance
“…Further, compared to women with no abuse, those who report childhood physical abuse have up to twice the odds of exhibiting eating disorders symptoms (Rayworth, Wise, & Harlow, 2004), and to have profound effects on body image issues that contribute to eating disorder symptoms (Treuer, Koperdák, Rózsa, & Füredi, 2005). Unusually high rates of lifetime sexual and physical abuse have been reported in women with comorbid EDs and substance use issues (Dworkin, 2018;Dworkin, Menon, Bystrynski, & Allen, 2017;Gilchrist, Gruer, & Atkinson, 2007). An addiction model that provides a framework for understanding how trauma increases the risk of SUDs is the 'selfmedication' hypothesis (Khantzian, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Further, compared to women with no abuse, those who report childhood physical abuse have up to twice the odds of exhibiting eating disorders symptoms (Rayworth, Wise, & Harlow, 2004), and to have profound effects on body image issues that contribute to eating disorder symptoms (Treuer, Koperdák, Rózsa, & Füredi, 2005). Unusually high rates of lifetime sexual and physical abuse have been reported in women with comorbid EDs and substance use issues (Dworkin, 2018;Dworkin, Menon, Bystrynski, & Allen, 2017;Gilchrist, Gruer, & Atkinson, 2007). An addiction model that provides a framework for understanding how trauma increases the risk of SUDs is the 'selfmedication' hypothesis (Khantzian, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence is shown to be one of the strongest predictors for the development of PTSD compared with other forms of trauma 910. A recent, well conducted systematic review (39 studies, more than 88 000 participants) reported a lifetime prevalence of PTSD after sexual assault of 36% (95% confidence interval 31% to 41%) 11. It can persist for many years, even with treatment 1213.…”
Section: What Are the Long Term Health Effects Of Sexual Violence?mentioning
confidence: 99%
“… 8 CSA is a violation of a child's sexual rights and therefore human rights 9 and can have a lasting impact on the survivors' well-being. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%